CODE MIXING IN HOKBEN RESTAURANT’S MENU CAMPUR KODE DI MENU RESTORAN HOKBEN - Sephany Johebeth; Arifuddin Arifuddin (Universitas Negeri Medan, 2021)
The objectives of this thesis is, firstly, to find out the kinds of code-mixing in the restaurant with daily conversation between crew and customer, and fellow crew. Secondly, to find out the factors make code mixing occurs. Thirdly, To find out the reason why do the customers use code mixing. This research was conducted from September 14th until September 15th 2020 in Hokben Sun Plaza. In this research, the researcher using research qualitative. Researcher explain the kinds of code mixing divided into 6 classifications by choosing theory from suwito (1985). The researcher collected the data by using unstructured interview and simple documentation like taking a voice recording. The result of this research showed the kinds of code mixing found in the words of data conversation between crew and customer and fellow crew, and find some factors make code mixing occurs in Hokben Restaurant.Keywords: Sosiolingustics, Code Mixing, Hokben Restaurant.